Application of Waqf in Modern Islamic Boarding School Darussalam Gontor, Ponorogo Regency in the Perspective of Sharia Economic Law and Law Number 41 of 2004 concerning Waqf - Taufik, Fikfik; Aprillillah, Yusi Nur Iman (Al-Muamalat: Jurnal Ekonomi Syariah, 2022)
Pondok Modern Darussalamm Gontor is an example of an educational institution that is successful in managing waqf by Nazir organizations. Because individual nazirs tend to be lay and they are afraid that waqf assets will not be managed properly. However, PMDG carries out waqf activities with the concept of fundraising, one of which is not regulated in Law No. 41 of 2004 concerning waqf, namely self waqf which is still used today. The research method used is a normative juridical approach. This research was conducted by examining library materials as the basic material for research, and by conducting a search on legislation and literature related to the problem under study. The basis of the implementation of this self-waqf is maqashid sharia, namely realizing benefit and avoiding harm. This is in accordance with the thinking of the Maliki School and the Hanafi School, with the background of its implementation being Law No. 41 of 2004 article 16 no. 3 point g. Therefore, self-waqf is still carried out because there is a noble goal, namely: to continue the leadership relay and PMDG ideals if the leader dies.